PERAN KUALITAS AUDIT DALAM MEMPERKUAT HUBUNGAN ANTARA SINYAL KEUANGAN DAN NILAI PERUSAHAAN (STUDI PADA SEKTOR FOOD AND BEVERAGE) - Listiana, Anggita; Cahyaningtyas, Niken Wahyu; Utami, Yuni (Jurnal Keuangan dan Bisnis, 2026)
Purpose: This study aims to examine the role of audit quality as a governance mechanism in strengthening the relationship between financial signals represented by profitability, leverage, and liquidity and firm value in the food and beverage sector. The analysis focuses on assessing whether audit quality enhances the credibility of financial information in shaping market perceptions of firm value. Design Methodology Approach: A quantitative approach is employed using purposive sampling of food and beverage companies listed on the Indonesia Stock Exchange over the observation period, resulting in panel data observations. Secondary data are obtained from published annual financial reports. The analysis is conducted using multiple linear regression to examine the direct effects of financial signals on firm value, while Moderated Regression Analysis  is applied to evaluate the moderating role of audit quality. Findings: The results indicate that profitability and liquidity have a positive and significant effect on firm value, whereas leverage has a negative and significant effect. Audit quality is found to strengthen the relationship between leverage and firm value, suggesting that high-quality audits reduce the perceived risk associated with debt structures. However, audit quality does not significantly moderate the relationship between profitability or liquidity and firm value, indicating that the credibility of these financial signals is less dependent on audit assurance. Practical Implications: Audit quality should be positioned as a critical governance mechanism that enhances the reliability of financial reporting, particularly in mitigating risks associated with leverage. Strengthening audit quality is expected to improve investor confidence in corporate financing decisions and overall firm valuation. Originality Value: This study provides empirical evidence on the selective moderating role of audit quality within the financial signaling framework affecting firm value. It contributes to the literature by clarifying inconsistencies in prior findings and highlighting that the effectiveness of audit quality is contingent upon the type of financial signal, particularly in the context of an emerging market and a sector sensitive to financial structure.